Effect of face mask on skin characteristics changes during the COVID‐19 pandemic - Park, Sae‐ra; Han, Jiyeon; Yeon, Yeong Min; Kang, Na Young; Kim, Eunjoo (Skin research and technology, 2021)
Background Previous studies have demonstrated the possibility of adverse effects of prolonged wearing of personal protective equipment in healthcare workers. However, there are a few studies about the effects on skin characteristics after wearing a mask for non‐healthcare workers. In this study, we evaluated the dermatologic effects of wearing a mask on the skin over time. Materials and Method Twenty‐one healthy men and women participated in the study. All participants wore masks for 6 hours consecutively. Three measurements were taken (a) before wearing the mask, (b) after wearing the mask for 1 hour, and (c) after wearing the mask for 6 hours. Skin temperature, skin redness, sebum secretion, skin hydration, trans‐epidermal water loss, and skin elasticity were measured. Results The skin temperature, redness, hydration, and sebum secretion were changed significantly after 1 and 6 hours of wearing a mask. Skin temperature, redness, and hydration showed significant differences between the mask‐wearing area and the non–mask‐wearing area. Conclusion Mask‐wearing conditions and time can change several skin characteristics. In particular, it is revealed that the perioral area could be most affected.